2020
DOI: 10.18662/po/11.2/168
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Eating Behaviors in Young Wrestlers

Abstract: The aim of this study is investigate the behaviors of young wrestlers. The scale of eating behavior was completed by 210 young wrestlers. T-test was used for statistical procedures. Average age of females were 17.52 and males were 17.90 in young wrestlers who participated in the study. There were statistically significant differences between both healthy eating behavior scores and unhealthy eating behavior scores of female and male wrestlers according to gender (p <0.05). According to gender, female and male s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Kesik 22 examined the nutritional knowledge levels and nutritional attitudes of university students and stated that there was no significant difference between male and female individuals 22 . Aksu et al 23 stated in their study that the healthy and unhealthy eating behaviors of wrestlers do not differ according to gender. However in our study a significant difference was found between the students who felt bad before the epidemic and those who felt well before the epidemic and their nutritional scores according to the levels they felt (p <0.05).…”
Section: Discussionmentioning
confidence: 89%
“…Kesik 22 examined the nutritional knowledge levels and nutritional attitudes of university students and stated that there was no significant difference between male and female individuals 22 . Aksu et al 23 stated in their study that the healthy and unhealthy eating behaviors of wrestlers do not differ according to gender. However in our study a significant difference was found between the students who felt bad before the epidemic and those who felt well before the epidemic and their nutritional scores according to the levels they felt (p <0.05).…”
Section: Discussionmentioning
confidence: 89%
“…Developing nations, like Ethiopia, confront substantial obstacles concerning malnutrition and non-communicable diseases, necessitating a concerted effort toward enhancing nutritional literacy and fostering healthy eating habits among adolescents ( 8 ). Ethiopia, in recent years, has witnessed a notable burden of malnutrition, overweight, and obesity, particularly within urban locales, largely attributed to a deficiency in nutritional knowledge ( 9 ).The perpetuation of inadequate dietary habits among adolescents can often be traced back to insufficient nutritional knowledge acquired during their formative years, predominantly influenced by familial and environmental factors ( 10 ).…”
Section: Introductionmentioning
confidence: 99%